Epidemiology of ocular allergy and co-morbidities in adolescents - Marcos Geraldini; Herberto Jose Chong Neto; Carlos Antonio Riedi; Nelson Augusto Rosário (Elsevier, 2013)
Objective: The prevalence of allergic conjunctivitis (AC) has not been established. Estimates suggest that ocular allergies affect 15% to 20% of the worldwide population, yet most epidemiological studies encompass nasal and ocular allergy symptoms and have not been specific to AC. The aim of this study was to verify the prevalence of ocular allergy symptoms, co-morbidities, and their impact on adolescents. Methods: Adolescents were selected from a sample of schools, and completed in classrooms a previously validated questionnaire on symptoms of AC. AC diagnosis was considered when more than three episodes of ocular itching were reported in the past 12 months. Related symptoms such as tearing, photophobia, foreign body sensation, impact on daily activities, and diagnosis of AC were analyzed. Results: Questionnaires were obtained from 3,120 adolescents (mean age 13.3 ± 1.1 years). Ocular itching in the past 12 months occurred in 1,592 (51%). The most frequently associated symptom was tearing (74%), followed by photophobia (50.1%) and foreign body sensation (37.1%). The prevalence of AC was 20.7%, affecting more females than males (56.1% versus 45.9%; p = 0.01). The risks of an adolescent with ocular allergy to present asthma, rhinitis, and atopic eczema were (OR = 5.7; 95% CI: 4.5 to 7.1), (OR = 3.6; 95% CI: 3.0 to 4.3), and (OR = 2.6; 95% CI: 2.0 to 3.5), respectively. Severe interference in daily activities was reported by 30.5%. Conclusions: Symptoms of ocular allergy are common, frequently associated to other allergic diseases, and impact the daily activities of adolescents. Resumo: Objetivo: A prevalência de conjuntivite alérgica (CA) não foi estabelecida. Estimativas sugerem que alergias oculares afetam de 15 a 20% da população mundial, ainda que a maioria dos estudos epidemiológicos abranjam sintomas de alergia nasal e ocular e não sejam específicos a respeito da CA. O objetivo deste estudo foi verificar a prevalência de sintomas, comorbidades e o impacto da alergia ocular em adolescentes. Métodos: Os adolescentes foram selecionados de uma amostra de escolas e preencheram, em sala de aula, um questionário previamente validado sobre os sintomas da CA. O seu diagnóstico foi considerado quando mais de três episódios de prurido ocular foram relatados nos últimos 12 meses. Sintomas relacionados, como lacrimejamento, fotofobia, sensação de corpo estranho, impacto sobre as atividades diárias e diagnóstico de conjuntivite alérgica, foram analisados. Resultados: Foram obtidos questionários de 3.120 adolescentes (média de 13,3 ± 1,1 ano). Nos últimos 12 meses, 1.592 (51%) adolescentes tiveram prurido ocular. O sintoma relacionado mais frequente foi lacrimejamento (74%), seguido de fotofobia (50,1%) e sensação de corpo estranho (37,1%). A prevalência de conjuntivite alérgica foi de 20,7%, afetando mais pessoas do sexo feminino do que do masculino (56,1% em comparação a 45,9%; p = 0,01). O risco de um adolescente com alergia ocular apresentar asma, rinite e eczema atópico foi (RC = 5,7; CI de 95%: 4,5 a 7,1); (RC = 3,6; CI de 95%: 3,0 a 4,3) e (RC = 2,6; CI de 95%: 2,0 a 3,5), respectivamente. Uma interferência grave nas atividades diárias foi relatada por 30,5%. Conclusões: Sintomas de alergia ocular são comuns, frequentemente relacionados a outras doenças alérgicas, e causam impacto sobre as atividades diárias de adolescentes. Keywords: Allergic conjunctivitis, Children, Epidemiology, Palavras-chave: Conjuntivite alérgica, Crianças, Epidemiologia